Aplikasi Bokashi Cair Berbahan Dasar Berbeda terhadap Pertumbuhan Sentro (Centrocema pubescens) - Maria Julia Dacosta Seran (JAS, 2021)
This research was conducted for 75 days, starting from early September to early November 2020 in the experimental garden of the Faculty of Agriculture, University of Timor. The purpose of this study was to determine the application of different based liquid bokashi to Sentro growth (Centrocema pubescens). The research method used in this study was a completely randomized design (CRD) consisting of 4 treatments and 4 replications so that there were 16 experimental units. The treatments given included R0 = without liquid bokashi, R1 = liquid bokashi made from beef feces, R2 = liquid bokashi made from goat feces, R3 = liquid bokashi made from chicken excreta. The variables tested included the number of leaves, stem diameter, and length of spread. The results of analysis of variance showed that the treatment given liquid bokashi from chicken excreta as a base material had a significant effect (P <0.05) where the liquid bokashi treatment from chicken excreta (R3) was better than those given liquid bokashi from other types, namely, with the number of leaves as much as 28.72 strands, stem diameter 0.29 cm, and length of spread 14.08. It can be concluded that the liquid bokashi made from chicken excreta produces good growth in Sentro (Centrocema pubencens) plants, namely with 18.72 leaves, 0.29 cm stem diameter, and 14.08 cm spread length.